2018
DOI: 10.1101/283044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytoplasmic sequestration of the RhoA effector mDiaphanous1 by Prohibitin2 promotes muscle differentiation

Abstract: Running title: Phb2 interacts with mDia1 in myotubesSummary statement: mDia1 has common and stage-specific functions in muscle cells. In myotubes, mDia1 is sequestered by an interacting protein Prohibitin2, which promotes Myogenin expression and mitigates mDia1's inhibitory effects on differentiation. (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/283044 doi: bioRxiv p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…Since formins also interact with microtubules, long‐distance mitochondrial transport is also sensitive to perturbation of formins (Gaillard et al, 2011). Mass‐spectrometric analysis has shown that mDia1 interacts with several components of the mitochondrial OxPhos complexes‐I, ‐II, ‐III, ‐IV, and ‐V, and influences mitochondrial biogenesis (Saleh et al, 2019). Although mDia1 strongly associates with prohibitin 2 (Phb2—an important regulator of mitochondrial bioenergetics) (Signorile et al, 2019), the experimental evidence for mDia1's involvement in mitochondrial OxPhos regulation is currently lacking in the literature.…”
Section: Bidirectional Communication Between Mitochondria and Actin C...mentioning
confidence: 99%
“…Since formins also interact with microtubules, long‐distance mitochondrial transport is also sensitive to perturbation of formins (Gaillard et al, 2011). Mass‐spectrometric analysis has shown that mDia1 interacts with several components of the mitochondrial OxPhos complexes‐I, ‐II, ‐III, ‐IV, and ‐V, and influences mitochondrial biogenesis (Saleh et al, 2019). Although mDia1 strongly associates with prohibitin 2 (Phb2—an important regulator of mitochondrial bioenergetics) (Signorile et al, 2019), the experimental evidence for mDia1's involvement in mitochondrial OxPhos regulation is currently lacking in the literature.…”
Section: Bidirectional Communication Between Mitochondria and Actin C...mentioning
confidence: 99%